2018
DOI: 10.5424/sjar/2018161-11916
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods for identifying anisotropy in the Spodoptera frugiperda spatial distribution

Abstract: Corn is a very important agricultural product, however, some pests may cause damage to the corn productivity such as Spodoptera frugiperda, which prevents the plant from growing in a regular manner. Since the indiscriminate use of the pesticide may cause an increasing resistance of the insect besides an environmental damage, it is important to estimate the areas and the dominant directions where the insect may propagate. The main aim of this work was to study the spreading of the fall armyworm in a commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…This indicated that armyworms spread in groups (consisting of several individuals), and the groups spread with a low grouping rate on the fields because the regression slope value is around 1. The spatial distribution pattern obtained from this study was similar to the study conducted by Rios et al (2014) in Southern Pernambuco state, Brazil, as well as the study result of Nava et al (2018). Intercept values (α) that are positive or greater than 0 might be due to the behavioral preferences of S. frugiperda that prefer certain spots in their habitat (leaf whorl) plus their characteristics of laying eggs in a group.…”
Section: Discussionsupporting
confidence: 89%
“…This indicated that armyworms spread in groups (consisting of several individuals), and the groups spread with a low grouping rate on the fields because the regression slope value is around 1. The spatial distribution pattern obtained from this study was similar to the study conducted by Rios et al (2014) in Southern Pernambuco state, Brazil, as well as the study result of Nava et al (2018). Intercept values (α) that are positive or greater than 0 might be due to the behavioral preferences of S. frugiperda that prefer certain spots in their habitat (leaf whorl) plus their characteristics of laying eggs in a group.…”
Section: Discussionsupporting
confidence: 89%